Comparison of Outcomes of Tricuspid Valve Surgery in Patients with Reduced and Normal Right Ventricular Function - Subbotina, Irina; Girdauskas, Evaldas; Bernhardt, Alexander M.; Sinning, Christoph; Reichenspurner, Hermann; Sill, Bjoern (The Thoracic and Cardiovascular Surgeon, 2017)
Background To study the effect of tricuspid valve repair/replacement on outcomes of patients with reduced systolic right ventricular function.Methods Between January 2012 and July 2016, 191 patients with isolated tricuspid valve regurgitation and/or in combination with other valve diseases were enrolled into this retrospective study. We compared early postoperative outcomes (i.e., 30 days after surgery) between patients' cohort with a preoperative reduced (i.e., at least moderately) versus normal (or mildly reduced) right ventricular function as defined by means of preoperative echocardiography.Results A total of 82 (43%) patients had preoperatively reduced right ventricle function with tricuspid annular plane systolic excursion (TAPSE) of 13.3 ± 3.3 versus 20.2 ± 4.9 mm (p < 0.001). Ring annuloplasty was the most common surgical technique (i.e., 91% in both groups). Time of procedure (317 ± 123 vs. 262 ± 88 minutes, p < 0.01) and time on cardiopulmonary bypass (163 ± 77 vs. 143 ± 57 minutes, p = 0.036) were significantly longer in patients with impaired right ventricular function. Postoperative lactate (3.5 ± 3 vs. 2 ± 1 mmol/L, p = 0.001) and dose of catecholamines (epinephrine, 0.07 ± 0.15 vs. 0.013 ± 0.02 µg/kg/min, p = 0.001; norepinephrine, 0.18 ± 0.23 vs. 0.07 ± 0.09 µg/kg/min, p = 0.007) were also higher in this group. Postoperative rate of low cardiac output syndrome (10 vs. 27%, p = 0.005) and early mortality (n = 2 vs. n = 9, p = 0.018) were significantly increased in patients with reduced right ventricular function. Previous cardiac operation (p = 0.045), preoperative higher number of acute decompensations of heart failure (p < 0.001), reduced right ventricular function (p = 0.018), postoperative low cardiac output syndrome (p < 0.001), and renal replacement therapy (p < 0.001) were identified as risk factors for early mortality. Echocardiography at discharge revealed tricuspid valve regurgitation grade of 0.9 ± 0.7 versus 0.7 ± 0.6 (p = 0.052) and TAPSE of 12 ± 3 versus 15 ± 5 mm (p = 0.026) in patients with reduced right ventricular function. The New York Heart Association (NYHA) class improved to 1.7 ± 0.7 versus 1.3 ± 1 (p < 0.001) in this group of patients.Conclusion Tricuspid valve repair/replacement effectively eliminated severe tricuspid regurgitation and improved clinical signs of heart failure. Although mortality and morbidity were increased in the group with reduced right ventricular function, even these patients benefitted from improved functional status and right ventricular systolic function early postoperatively.
Keywords: tricuspid valve; outcomes; surgery; reduced right ventricular function